Call for Papers for the 2023 SSLLT Conference - ssllt, ssllt (Studies in Second Language Learning and Teaching, 2022)
The main aim of the event is to celebrate the success of the journal Studies in Second Language Learning and Teaching (https://pressto.amu.edu.pl/index.php/ssllt), which was launched little over a decade ago but has still managed to be ranked among the best journals in the field. The event will also provide a forum for presenting cutting-edge research related to different facets of L2 learning and teaching in a wide range of contexts and demonstrating how the results of such research can inform everyday classroom practices. The conference will be of high relevance to academics, researchers, teacher educators and materials writers, as well as language teachers at different educational levels wishing to enhance their instructional practices.